2014
DOI: 10.1088/1009-0630/16/8/10
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Automatic Process of Edge Rotation Diagnostic System on J-TEXT Tokamak

Abstract: A spectral diagnostic control system (SDCS) is developed to implement automatic process of the edge rotation diagnostic system on the J-TEXT tokamak. The SDCS contains a control module, data operation module, data analysis module, and data upload module. The core of this system is a newly developed software "Spectra Assist", which completes the whole process by coupling all related subroutines and servers. The results of data correction and calculated rotation are presented. In the daily discharge of J-TEXT, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Wu et al 7) observed the shape of the longgap-distance vacuum arc of a coil-type electrode and found that with increasing gap distance, the radius of the arc column increases near the cathode but decreases near the anode. Cheng et al [8][9][10] studied the long-gap-distance vacuum arc of different electrodes, and found that arc stability is related to gap distance, arc current, as well as the intensity and phase shift of the imposed axial magnetic field. Xiu et al 3) revealed the distortion phenomenon of the long-gap-distance vacuum arc and studied the relevant factors of arc distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al 7) observed the shape of the longgap-distance vacuum arc of a coil-type electrode and found that with increasing gap distance, the radius of the arc column increases near the cathode but decreases near the anode. Cheng et al [8][9][10] studied the long-gap-distance vacuum arc of different electrodes, and found that arc stability is related to gap distance, arc current, as well as the intensity and phase shift of the imposed axial magnetic field. Xiu et al 3) revealed the distortion phenomenon of the long-gap-distance vacuum arc and studied the relevant factors of arc distortion.…”
Section: Introductionmentioning
confidence: 99%